FORMATION OF PROFESSIONAL AND PERSONAL SUCCESSFULNESS OF FUTURE EDUCATIONAL PSYCHOLOGISTS IN THE EDUCATIONAL PROCESS AT UNIVERSITY - Shalaginova, Kseniea; Panferova, Elena; Dekina, Elena; Shelispanskaja, Ellada (Revista Inclusiones, 2020)
The relevance of the study is due to the need to search for innovative technologies for training psychological and pedagogical personnel. The basis of the research is an integrative approach aimed at updating the processes of professional self-knowledge; the development of individuality; mastering the techniques of improvement and development of professionally important qualities; building an individual trajectory of development. The study of the features of the formation of professional and personal successfulness was carried out using a diagnostic program aimed at determining emotional stability, success motivation, level of sociability, etc. The study involved 50 senior students of the psychology department. The work is aimed at identifying ways and means of shaping students’ professional and personal successfulness in order to solve the main task of this age period — the development of individuality. The presented program sets benchmarks for and contributes to the understanding of the purpose of the profession, professional goal-setting and goal-achievement, to the support of student initiatives, building a professional career, and developing mentoring in higher school. The program is based on the fact that for educational psychologists it becomes important to develop the diverse abilities of students, their universal competences. For this, the future specialists should gain experience while studying at the university. The conducted research deepens the modern understanding of the technologies of shaping the professional and personal successfulness of future specialists.